KARAKTER MAHASISWA WIRAUSAHA DI ERA DIGITAL MARKETING: LITERATURE REVIEW - Arief Syahreza; Nyimas Ema Holiza (JURNAL LENTERA BISNIS, 2023)
This article employs qualitative research methods, specifically literature research, utilizing 25 data sources including books, journals, and conference proceedings, both nationally accredited in Sinta and internationally indexed in Scopus, published within the past decade. These sources were scrutinized, analyzed, and synthesized to explore various aspects of fostering independent student entrepreneurship in the context of digital marketing. The literature review has revealed seven primary themes, encompassing entrepreneurship education, factors influencing entrepreneurship, educational implications, digital marketing, business development, women's entrepreneurship, and mentoring. These findings underscore the significance of fostering traits such as creativity, emotional intelligence, and adaptability in response to the ever-evolving entrepreneurial landscape. They also emphasize the necessity of establishing robust integration between conceptual frameworks, entrepreneurial ecosystems, and mentoring programs. As a result of this review, recommendations include encouraging students to actively engage in entrepreneurial education, advocating for community support of local entrepreneurs by purchasing their products, and urging academics to continually update entrepreneurship curricula while incorporating project-based learning methods. Moreover, collaboration with both industry and governmental entities is essential for creating a more inclusive entrepreneurial ecosystem. Key words: Character, Digital Marketing, Literature Review